Mediastinum - Stephens, Shiby (Henry Stewart Talks, 2020)
Definition of the mediastinum, The major divisions of mediastinum: superior and inferior, The subdivisions of mediastinum: posterior, anterior and middle mediastinum, The contents of mediastinum